Repeatability and Specificity of Eccentric Force Output and the Implications for Eccentric Training Load Prescription. Issue 3 (March 2019) - Harden, Mellissa; Wolf, Alex; Haff, G. Gregory; Hicks, Kirsty M.; Howatson, Glyn
Abstract : Abstract: Harden, M, Wolf, A, Haff, GG, Hicks, KM, and Howatson, G. Repeatability and specificity of eccentric force output and the implications for eccentric training load prescription. J Strength Cond Res 33(3): 676–683, 2019—Prescribing supramaximal eccentric (ECC) loads based on repetition maximum, isometric (ISO), or concentric-only (CON) strength overlooks the possibility that individuals have a different tolerance for ECC exercise. To inform the prescription of ECC training regimes, this study implemented a test battery that included maximal accentuated-eccentric (ECC+), traditional coupled eccentric-concentric (TRAD), and 2 ISO conditions (90 and 120° knee-joint angle [ISO90 and ISO120, respectively]). The study aimed to determine the repeatability and specificity of ECC+ force output and assess the methodological accuracy when using nonspecific measures of strength to prescribe ECC+ training loads. Results show that the test battery was repeatable ( p > 0.05, intraclass correlation coefficient >0.95, coefficient of variation: <5.8%) and force output was specific to each task; ECC+ (4, 034 ± 592 N) was higher ( p < 0.001) than ISO90 (3, 122 ± 579 N) and TRAD (3, 574 ± 581 N), but less ( p < 0.001) than ISO120 (6, 285 ± 1, 546 N). Although estimations of ECC+ strength were not different from observed ECC+ values ( p > 0.05), estimations were associated with up to a 7% error. This investigation confirms that force output is task-specific; therefore, prescribing ECC loads based on strength during another task will likely lead to discrepancies in intended and actual ECC exercise intensity. Consequently, using an ECC-specific approach to assess ECC strength qualities will provide a more accurate platform to prescribe individualized ECC training programs and a more definitive evaluation of ECC strength.